Limestone calcined clay cement as a low-carbon solution to meet expanding cement demand in emerging economies. (2017) - Cancio Díaz, Yudiesky; Sánchez Berriel, Sofia; Heierli, Urs; Favier, Aurélie R.; Sánchez Machado, Inocencio R.; Scrivener, Karen L.; Martirena Hernández, José Fernando; Habert, Guillaume
Abstract: This paper aims at assessing the return on investment and carbon mitigation potentials of five investment alternatives for the Cuban cement industry in a long-term horizon appraisal (15 years). Anticipated growing demand for cement, constrained supply and an urgent need for optimisation of limited capital while preserving the environment, are background facts leading to the present study. This research explores the beneficial contribution of a new available technology, LC 3 cement, resulting from the combination of clinker, calcined clay and limestone, with a capacity of replacing up to 50% of clinker in cement. Global Warming Potential (GWP) is calculated with Life Cycle Assessment method and the economic investment's payback is assessed through Return on Capital Employed (ROCE) approach. Main outcomes show that projected demand could be satisfied either by adding new cement plants—at a high environmental impact and unprofitable performance— or by introducing LC 3 strategy. The latter choice allows boosting both the return on investment and the production capacity while reducing greenhouse gas (GHG) emissions up to 20–23% compared to business-as-usual practice. Overall profitability for the industry is estimated to overcome BAU scenario by 8–10% points by 2025, if LC 3 were adopted. Increasing the production of conventional blended cements instead brings only marginal economic benefits without supporting the needed increase in production capacity. The conducted study also shows that, in spite of the extra capital cost required for the calcination of kaolinite clay, LC 3 drops production costs in the range of 15–25% compared to conventional solutions.